2007
DOI: 10.1073/pnas.0707349104
|View full text |Cite
|
Sign up to set email alerts
|

Coevolutionary networks of splicing cis -regulatory elements

Abstract: Accurate and efficient splicing of eukaryotic pre-mRNAs requires recognition by trans-acting factors of a complex array of cis-acting RNA elements. Here, we developed a generalized Bayesian network to model the coevolution of splicing cis elements in diverse eukaryotic taxa. Cross-exon but not cross-intron compensatory interactions between the 5 splice site (5 ss) and 3 splice site (3 ss) were observed in human/mouse, indicating that the exon is the primary evolutionary unit in mammals. Studied plants, fungi, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
50
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(65 citation statements)
references
References 48 publications
15
50
0
Order By: Relevance
“…The greater effect of the 5 ′ SS suggests a more critical role of its sequence, as has been suggested before (Xiao et al 2007). …”
supporting
confidence: 57%
See 1 more Smart Citation
“…The greater effect of the 5 ′ SS suggests a more critical role of its sequence, as has been suggested before (Xiao et al 2007). …”
supporting
confidence: 57%
“…It also allowed us to add multiple copies of an ESE while not adding any sequences that were not already present in a single ESE DE. It has been shown that the ESE strength or number inversely correlates with splice site strength in mammalian exons, i.e., ESEs can compensate for weak splice sites (Xiao et al 2007;Ke et al 2008). In addition, Hertel and Maniatis (1998) showed that the use of multiple downstream enhancer elements increased the use of a 3 ′ SS in an additive manner when tested in vitro .…”
Section: Des: Effect Of Multiple Esesmentioning
confidence: 99%
“…Canonical splicing (i.e., linear splicing) of most metazoan introns requires a stepwise assembly of spliceosomal components in a cotranscriptional fashion (Kornblihtt et al 2013;Matera and Wang 2014), starting with a process called exon definition in which the 5 ′ ss and 3 ′ ss are recognized in pairs across exons through the interaction of U1 and U2 snRNPs (Fox-Walsh et al 2005;Xiao et al 2007). In a subsequent transition, U1 and U2 snRNPs undergo rearrangements to form an intron-spanning interaction known as intron definition complex (De Conti et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The intron definition model is often used to describe mechanism of splicing of large internal exons flanked by at least one small intron. 30,[35][36][37][38] Based on the wealth of information accumulated to date, we propose that splicing of SMN2 exon 7 is driven by the intron definition mechanism. Of note, much of the results described here pertain to the widely studied SMN intron 7, which is only 444-nt long.…”
Section: Intron Retention Supports Intron Definition Modelmentioning
confidence: 99%